PROCEDURE FOR ORGANIZATION AND CANCELLATION OF A LIMITED LIABILITY COMPANY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article defines the concept of LLC in the current legislation, the problems and proposals in practice, as well as the legal status and scope of responsibilities of its participants, different approaches of scholars in this regard and the improvement of civil law regulation of the LLC. Scientific and theoretical problems of the civil status of LLC on the basis of the legislation of the Republic of Uzbekistan, the concept and essence of LLC, its role and importance in the system of civil law entities, legal entities and business societies.